2019
DOI: 10.1016/j.athoracsur.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Binding Protein in Adult Heart Surgery

Abstract: Background. Heparin binding protein (HBP) is released from neutrophilic secretory vesicles upon neutrophil adhesion on the endothelium. HBP mediates capillary hyperpermeability experimentally. In sepsis, HBP predicts organ dysfunction. Cardiopulmonary bypass induces both neutrophil activation and hyperpermeability. We hypothesized that in cardiopulmonary bypass, HBP is released in the reperfused coronary circulation concomitantly with neutrophil adhesion. Methods. In 30 patients undergoing aortic valve replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Extracorporeal membrane oxygenation (ECMO) would be initiatively implemented in the operating room if patients had refractory hypotension and met the following conditions [15]: ① long CPB time (CPB time of > 4 h); ② need for high-dose vasoactive drugs (vasoactive-inotropic score ≥ 40); ③ cardiac index of < 2.2 L/ m 2 /min and MAP of < 60 mmHg; ④ arterial lactate level of > 5 mmol/L; and ⑤ failure in weaning from CPB. A recent study reported that HBP was released from reperfused coronary circulation concomitantly with coronary neutrophil adhesion and myocardial injury [21]. This finding may suggest that compared with arterial HBP, the HBP drawn from CS may be a more sensitive method for the intraoperative assessment of myocardial injury.…”
Section: Patient Management Sample Collection and Biomarker Assaysmentioning
confidence: 98%
See 2 more Smart Citations
“…Extracorporeal membrane oxygenation (ECMO) would be initiatively implemented in the operating room if patients had refractory hypotension and met the following conditions [15]: ① long CPB time (CPB time of > 4 h); ② need for high-dose vasoactive drugs (vasoactive-inotropic score ≥ 40); ③ cardiac index of < 2.2 L/ m 2 /min and MAP of < 60 mmHg; ④ arterial lactate level of > 5 mmol/L; and ⑤ failure in weaning from CPB. A recent study reported that HBP was released from reperfused coronary circulation concomitantly with coronary neutrophil adhesion and myocardial injury [21]. This finding may suggest that compared with arterial HBP, the HBP drawn from CS may be a more sensitive method for the intraoperative assessment of myocardial injury.…”
Section: Patient Management Sample Collection and Biomarker Assaysmentioning
confidence: 98%
“…Therefore, blood samples were directly taken from the CS by surgeons and simultaneously drawn from the arterial line of the CPB by perfusionists. Moreover, the blood samples for research were drawn at two time points: ① time point 1: immediately before aortic cross-clamping; and ② time point 2: 5 min after aortic declamping [21]. It should be emphasized that the CS samples were obtained after ligaturing cannulations of the superior and inferior vena cava.…”
Section: Patient Management Sample Collection and Biomarker Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, two studies have described HBP levels in cardiac surgery. Pesonen et al showed a 39fold increase in HBP concentration during cardiac surgery with CPB and Pan et al demonstrated that elevated HBP levels after the release of cross-clamp predicted myocardial injury related cardiogenicshock after cardiac surgery (13,16). However, neither study did fully describe the intra-and postoperative dynamics of HBP or investigate whether the administration of heparin and protamine have any effect on HBP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Pesonen et al recently showed that HBP is increased during cardiac surgery with CPB (13). However, the effects of heparin and protamine were not investigated, and neither were the postoperative dynamics of HBP.…”
Section: Introductionmentioning
confidence: 99%